Redox-Active Mn Porphyrin-based Potent SOD Mimic, MnTnBuOE-2-PyP(5+), Enhances Carbenoxolone-Mediated TRAIL-Induced Apoptosis in Glioblastoma Multiforme - Yulyana, Yulyana; Tovmasyan, Artak; Ho, Ivy A W; Sia, Kian Chuan; Newman, Jennifer P; Ng, Wai Hoe; Guo, Chang Ming; Hui, Kam Man; Batinic-Haberle, Ines; Lam, Paula Y P (Stem cell reviews and reports, 2016)
Glioblastoma multiforme is the most malignant tumor of the brain and is challenging to treat due to its highly invasive nature and heterogeneity. Malignant brain tumor displays high metabolic activity which perturbs its redox environment and in turn translates to high oxidative stress. Thus, pushing the oxidative stress level to achieve the maximum tolerable threshold that induces cell death is a potential strategy for cancer therapy. Previously, we have shown that gap junction inhibitor, carbenoxolone (CBX), is capable of enhancing tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) -induced apoptosis in glioma cells. Since CBX is known to induce oxidative stress, we hypothesized that the addition of another potent mediator of oxidative stress, powerful SOD mimic MnTnBuOE-2-PyP(5+) (MnBuOE), could further enhance TRAIL-driven therapeutic efficacy in glioma cells. Our results showed that combining TRAIL + CBX with MnBuOE significantly enhances cell death of glioma cell lines and this enhancement could be further potentiated by CBX pretreatment. MnBuOE-driven cytotoxicity is due to its ability to take advantage of oxidative stress imposed by CBX + TRAIL system, and enhance it in the presence of endogenous reductants, ascorbate and thiol, thereby producing cytotoxic H2O2, and in turn inducing death of glioma cells but not normal astrocytes. Most importantly, combination treatment significantly reduces viability of TRAIL-resistant Asian patient-derived glioma cells, thus demonstrating the potential clinical use of our therapeutic system. It was reported that H2O2 is involved in membrane depolarization-based sensitization of cancer cells toward TRAIL. MnBuOE is entering Clinical Trials as a normal brain radioprotector in glioma patients at Duke University increasing Clinical relevance of our studies.